The leaching behaviour of Cu, Zn and Pb from waste printed circuit boards by [BSO4HPy]HSO4. (21st November 2019) - Zhang, Sha; Chen, Mengjun; Wang, Jiqin; Wang, Bin; Huang, Jinxiu; Chen, Shu
Currently, researches are mainly focused on how to recycle valuable metals from waste printed circuit boards (WPCBs), but rarely on the toxic substances, such as zinc and lead, during the recycling process. In this research, the effect of zinc and lead during the process of leaching copper from WPCBs by an acidic ionic liquid (IL), N-sulfobutylpyridinium hydrosulphate ([BSO4 HPy]HSO4 ), was investigated in detail. Results showed that copper and zinc could be successfully leached out by [BSO4 HPy]HSO4 . When 1 g of 0.1 to 0.25 mm WPCBs powder was leached by 25 mL of 80% (v/v) ionic liquid and 10 mL of 30% hydrogen peroxide at 40°C for 2 h, copper and zinc leaching rate could be up to 99.75% and 93.02%, respectively. H2 O2 added amount, solid-liquid ratio and temperature could significantly impact the leaching rate of copper and zinc. On the contrary, lead leaching rate is hardly influenced by these factors, maintaining at around 2%. Thus, during the leaching process, zinc could significantly influence the leaching of copper, which was totally different for lead. Leaching kinetics analysis indicated that the leaching of copper and zinc is controlled by solid film diffusion, and the leaching of lead is controlled by chemical reaction.